Novel heterozygous compound TRMT5 mutations associated with combined oxidative phosphorylation deficiency 26 in a Chinese family: a case report - Shuiyan Wu; Weixi Li; Zhenjiang Bai; Saihu Huang; Daoping Yang; Hongmei Chen; Ying Li; Ying Liu; Haitao Lv (BMC Pediatrics, 2022)
Abstract Background Combined oxidative phosphorylation deficiency 26 (COXPD26) is an autosomal recessive disorder characterized by early onset, developmental delay, gastrointestinal dysfunction, shortness of breath, exercise intolerance, hypotonia and muscle weakness, neuropathy, and spastic diplegia. This disease is considered to be caused by compound heterozygous mutations in the TRMT5 gene. Case presentation In this study, we report a female child with COXPD26 manifesting as shortness of breath, gastrointestinal dysmotility, severe developmental delay, muscle hypotonia and weakness, exercise intolerance, renal and hepatic defects, and recurrent seizures with spastic diplegia. Interestingly, the hepatic feature was first observed in a COXPD26 patient. Medical exome sequencing with high coverage depth was employed to identify potential genetic variants in the patient. Novel compound heterozygous mutations of the TRMT5 gene were detected, which were c.881A>C (p.E294A) from her mother and c.1218G>C (p.Q406H) and c.1481C>T (p.T494M) from her father. Conclusion The newly emerged clinical features and mutations of this patient provide useful information for further exploration of genotype–phenotype correlations in COXPD26.